The Politics of the Military’s Dual Function: Practices of Autocratic Legalism in the Revision of the TNI Law - Eivandro Wattimury; Madaskolay Viktoris Dahoklory (Legtimacy: Journal of Law and Islamic Law, 2026)
Following the 1998 Reformation, the Constitution and Law Number 34 of 2004 explicitly separated military roles from the political sphere to abolish ABRI’s Dual Function. However, this constitutional demarcation is undermined by the Prabowo-Gibran administration's maneuver of appointing an active-duty officer, Major Teddy, as Cabinet Secretary. This juridical-normative research analyzes said phenomenon as a practice of autocratic legalism within the Revision of the TNI Law. The study concludes that this revision is not merely an administrative adjustment, but a legalization strategy to justify military intervention in civil positions previously strictly prohibited. By manipulating legal instruments through closed legislative processes that ignore meaningful public participation, the government unilaterally legitimizes such unconstitutional actions. This statute becomes an autocratic tool to blur civil-military boundaries, weaken the rule of law, and restore military dominance within the civil administration structure. This phenomenon proves law is misused to serve executive power, marking a serious regression in Indonesia's constitutional democratic consolidation.